Simulation Modeling in Digital Radiography with Allowance for Spatial Outlines of Test Objects; Russian Journal of Nondestructive Testing; Vol. 56, iss. 8 - Osipov S. P. Sergey Pavlovich; Chakhlov S. V. Sergey Vladimirovich; Yadrenkin I. G. Iljya Gennadjevich; Osipov O. S. Oleg Sergeevich; Usachev E. Yu. Evgeny Yurjevich (2020, 2020)
Title screen